Persepsi Visual dan Konstruksi Makna Spiritualitas pada Prasasti Telaga Batu: Analisis Arnheimian Terhadap Simbol Air, Batu, dan Ular - Yulius, Yosef; Suryanegara, Erwan; Patriansah, Mukhsin; Amalia, Shalyna Nadya; Ubaidillah, Muhammad (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2025)
This study aims to understand how the visual elements of the Telaga Batu Inscription shape visual perception and spiritual meaning within the cultural context of the Sriwijaya Kingdom. The research applies Rudolf Arnheim’s visual perception theory, which defines seeing as an active mental process that organizes balance, direction, and structure to generate meaning. The method used is descriptive qualitative with visual analysis of three main elements of the inscription, namely stone, water, and serpent. Data were collected through literature review and visual documentation, then analyzed to identify principles of balance, rhythm, and unity that construct spiritual experience within the ritual of oath-taking. The results show that the Telaga Batu Inscription was designed with strong visual awareness to evoke a sense of sanctity and royal authority. The stone symbolizes stability and eternity, water functions as a medium of purification, and the seven-headed serpent represents cosmic protection. These elements together form a spiritual visual communication system that reinforces the values of loyalty and power in Sriwijaya. The findings demonstrate that visual perception theory can be applied to interpret ancient artifacts as visual communication designs carrying profound spiritual and cultural values.